Pseudo-Probabilistic Design for High-Resolution Tsunami Simulations in the Southwestern Spanish Coast - González, Alejandro; Fernández Hernández, Marta; Llorente Isidro, Miguel (MPDI, 2022)
The application of simulation software has proven to be a crucial tool for tsunami hazard assessment studies. Understanding the potentially devastating effects of tsunamis leads to the development of safety and resilience measures, such as the design of evacuation plans or the planning of the economic investment necessary to quickly mitigate their consequences. This article introduces a pseudo-probabilistic seismic-triggered tsunami simulation approach to investigate the potential impact of tsunamis in the southwestern coast of Spain, in the provinces of Huelva and Cádiz. Selected faults, probabilistic distributions and sampling methods are presented as well as some results for the nearly 900 Atlantic-origin tsunamis computed along the 250 km-long coast.
Keywords: Maremotos; Simulation; Seismic faults; Sobol sampling; Pseudo-probabilistic